Effect of hybrid FRP confinement on tin slag polymer concrete compressive strength - Muhamad Soffi, Manda; Mohd Ruzaimi, Mat Rejab; Shukur, Abu Hassan; Mat Uzir, Wahit (Blue Eyes Intelligence Engineering and Sciences Engineering and Sciences Publication, 2023)
This study investigates the strength enhancement of Tin Slag Polymer Concrete (TSPC) under hybrid GFRP and CFRP confinement in comparison with mono GFRP and CFRP confinement on TSPC circular short column samples. Hybrid FRP confinement is prepared by wrapping TSPC with GFRP followed by CFRP both 1 layer using epoxy Sikadur 330 as matrix binders with 50 mm overlap. Compression test was performed on unconfined TSPC (TSPC-UC), TSPC with GFRP confinement (TSPC-GF), TSPC with CFRP confinement (TSPC-CF) and TSPC with hybrid FRP confinement (TSPC-HB) with 1mm/ min loading rate. The test results have revealed that the ultimate strengths are 59.19 MPa (TSPC-UC), 85.54 MPa (TSPC-GF), 108.77 MPa (TSPC-CF) and 124.59 MPa (TSPC-HB). The corresponding compressive strain measured at ultimate compressive strength is 0.0300 (TSPC-UC), 0.0453 (TSPC-GF), 0.0398 (TSPC-CF) and 0.0588 (TSPC-HB). Stress versus strain curve has shown that compared to TSPC-UC, externally strengthen sample with GFRP, CFRP and Hybrid FRP have enhanced TSPC strength with slight different behavior. TSPC-GF has less strength enhancement with larger strain while TSPC-CF provide larger strength enhancement but with lower strain. However, TSPC-HB has shown the highest strength enhancement with larger strain benefit from combined GFRP and CFRP properties. Failure mode of hybrid FRP confinement on TSPC (TSPC-HB) has shown combination of both FRP components failure mode (TSPC-GF and TSPC-CF) as in rupture pattern and delamination. The results of this study has provide findings on the effect of hybrid FRP confinement on TSPC circular column sample in close expectation based on literatures.